Anomalies presented by Haemonchus contortus (nematoda, trichostrongylidae) - Santiago, Marco A. M. (Pesquisa Agropecuaria Brasileira, 2014)
Haemonchus contortus, presenting abnormalities of the genital structures were found in sheep and cattle in Rio Grande do Sul, Brazil. These abnormalities were observed to be quite common. An experiment was conducted, using lambs with altered rumen and abomasal physiology, in an attempt to determine how the teratological phenomenon occurred. From the results, it was hypothesized that an abnormal development of H. contortus is produced by an altered environment or physiology of the digestive organs at the time the larvae are developing.